Menanggulangi Kenakalan Remaja Melalui Kegiatan Remaja Masjid - Muthoharoh Muthoharoh; Yusri Yusri; Suteja Suteja (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2022)
Juvenile delinquency behavior is the background of this research, adolescents need religious teachings, moral values and social values. For this reason, mosque youth administrators function as a forum for the process of forming Islamic youth and show their dedication as future generations who are responsible for themselves, the nation and religion. This study aims to understand how to deal with juvenile delinquency by mosque youth activities as an effort to prevent it. This type of descriptive research with a qualitative approach and data collection techniques with interviews, observation and documentation are the methods used in this study. This study found the fact that the Baitul Muttaqien Jami’ Mosque Youth Association had succeeded in tackling juvenile delinquency in the village of Banjaran, Sumberjaya sub-district by involving teenagers in events organized by the mosque's youth administrators including recitation, social services, sponsoring orphans and celebrating Islamic holidays. Through these activities, the behavior of adolescents gradually leads to be better by leaving bad behaviors and habits.